The Complexity of the His Bundle: Understanding Its Anatomy and Physiology through the Lens of the Past and the Present. Issue 12 (20th September 2016) - DANDAMUDI, GOPI; VIJAYARAMAN, PUGAZHENDHI
Abstract : In this paper, we describe the anatomy and physiology of the His bundle and describe the mechanisms by which permanent His‐bundle pacing can be accomplished.